The Concept of Adab Education and Its Relevance to Islamic Education in The Era of Society 5.0 : Analysis of The Interpretation of Surah Al Kahfi - Muhammad Idris; Mustafa, Mustafa; Hambali Jaili; Alven Putra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Technological advances have brought about significant changes and influences in all aspects of human life, including in matters of etiquette. This comprehensive study interprets the concept of etiquette education in Surah al-Kahf and its relevance to Islamic education in the Society 5.0 era. This study was library research using a thematic surah approach. Primary data sources included the Quran and Hadith, tafsir books, and journal articles, while secondary sources were taken from other relevant books. Data analysis used content analysis and comparative analysis, with validity checked using triangulation techniques. The research findings showed that first, etiquette must be possessed by learners, namely educators, students, and simultaneously (educators and students. For students: 1) making maximum effort in seeking knowledge, 2) needing rest time during the process of seeking knowledge, and 3) speaking politely to teachers. For educators: answering students' questions politely. For both educators and students: 1) having an agreement in the educational process, 2) having a strong commitment to the agreement, and 3) having a separation. Second, no matter how advanced technology is today, the educational process must prioritize etiquette because etiquette can shape an education that is a blessing for all creation, and the realization of the perfect human being.